Analysis of the Effect of High Molecule Components on the Realogy of Oil Disperser Systems - Nurullayev, V.H.; Gurbanov, H.R.; Abdullayeva, Z.A. (Herald of Azerbaijan Engineering Academy, 2022)
On the basis of numerous studies the anomalous changes of rheophysical featuuers of different crude oil mixes were investigated. It was defined that one of the main reasons for the anomaly is the variety of chemical composition and structure of miscible crude oils. We have established the mechanism of the effect of structural-group and fractionaloil content on its physicochemical properties and theological characyeristics resulting from a high content of high molecular components due to different solubility of liquid hydrocarbons relative to the latter ones.